Struktur Struktur Sistem Pemadam Otomatis Dan Pemantauan Kebakaran Kapal Berbasis Internet of Things - ian mochamad sofian (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Many factors cause ship accidents, one of the main causes comes from human error. In addition, events that cause delays in handling fires are delays in information for ship fire warnings. To solve the problem, we conduct research so that ship fires can be quickly detected automatically and monitored from afar. A common problem is that in the territorial waters there is no data communication network so it is difficult to convey information in the event of a ship fire. Therefore, we designed the automatic extinguishing and monitoring of ship fires using LoRa. The detector can activate the APAR automatically if there is a fire and notify on the ground. The ship's fire detector consists of: Arduino Uno, LoRa module, esp, flame, MQ-2, ds18b20. The LoRa configuration applied is BW=125, CR=4/5, and SF=12. With this configuration, our experiment can send data to a LoRa gateway that is 50 m from the sensor node. Meanwhile, the RSSI level received by the gateway is -112.